HUBUNGAN POLA KONSUMSI PANGAN DAN AKTIVITAS FISIK DENGAN KEKUATAN DAN DAYA TAHAN TARUNA AKADEMI IMIGRASI DEPOK, JAWA BARAT - Meirisa Rahmawati; Hadi Riyadi (Food and Nutrition Society of Indonesia, 2013)
This study was aimed to observe association between consumption pattern and physical activity with strength and endurance of taruna in Immigration Academy, Depok, West Java. A cross sectional study using 63 taruna as study participant was conducted. The results of study showed that there was significant correlation between nutritional status and strength of taruna (p<0.05). There was no significant correlation between adequacy levels of energy, protein, fat, carbohydrate, calcium, iron, vitamin A, vitamin B1, vitamin C, physical activity with strength and endurance (p>0.05). There was no significant correlation between nutritional status with endurance of taruna (p>0.05).